Facilitating Overdose Risk Mitigation Among Patients Following a Clinician Office Closure: A Connecticut Case Study of the Opioid Rapid Response Program. Issue 6 (November 2022) - Rubel, Stephanie K.; Neubert, Patrick; Navarretta, Nancy; Logan, Susan
Abstract : The Opioid Rapid Response Program (ORRP) is a federal program designed to support states in mitigating risks to patients who lose access to a prescriber of opioids or other controlled substances. Displaced patients might face risks of withdrawal, overdose, or other harms. Rapid response efforts to mitigate risks require coordination across multiple parts of the health care system. This case study describes an ORRP-coordinated event, including notification from law enforcement, information sharing with state health officials, state-coordinated response efforts, key observations, and lessons learned. Timely risk mitigation and care continuity required coordination between law enforcement and public health in advance of the disruption and throughout the state-led response. Patients' acute and prolonged health care needs were complex and highlight the importance of investing time and resources in coordinated, multisector state and local preparedness for these types of disruptions.